Effect of dietary energy and protein levels on growth and carcass characteristics of straight run hilly chicken up to eight weeks of age reared in confinement - Khatun, Halima; Mostafa, Md Golam; Islam, Md Nazrul (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The experiment was undertaken to determine the effect of varying energy and protein levels on growth performance and carcass characteristics of hilly chicks at starting period. Three hundred twenty-four straight run day-old chicks were randomly allocated to three dietary treatments of varying energy and protein levels as 2850, 2950 and 3050 ME Kcal/Kg and 200, 210 and 220 g CP/kg DM for starting period. Feed intake, live weight gain, feed conversion, digestibility and dressing percentage were measured during the experimental period. Final body weight and body weight gain were not significantly affected (P>0.05) by the dietary regimes and its interaction. Birds consumed least amount of feed on the diet containing 2850 kcal/kg energy (P<0.01) and convert feed comparatively with better efficiency (P<0.05). However, protein efficiency was better (P<0.05) at the lower level of dietary protein (20% CP) and energy (2850 ME Kcal/kg). At 20% of CP level, increasing dietary energy from 2850 to 3050 kcal/kg ME resulted into a 29g decreases in weight gain. Conversely, at 2850 kcal/kg ME an increase in dietary protein from 20% to 22% CP resulted into a 27 g decrease in weight gain. Maximum weight gain was achieved at an ME: CP ratio of 142.5 which corresponded with the 2850 kcal/kg ME and 20% CP diet. Birds fed with 2850 kcal/kg energy diet had higher carcass weight (P<0.001) compared to other energy level. Fed on the diets with the lower energy level (2850 kcal/kg ME) yielded the heaviest breast meat (P<0.01) and thigh meat (P<0.05). The findings of present study therefore indicate that the 2850 kcal/kg ME and 20% CP dietary level, with ME: CP ratio of 142.5 could meet the growth performance of the indigenous hilly chicken. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 464-470